2012
DOI: 10.1177/0261429412440649
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in fine motor skills and their influence on persistence among gifted elementary school pupils

Abstract: This article addresses the causes of underachievement in scholastic education. Whereas many studies have been able to show that motivational deficits provide an explanation for underachievement, little research has yet explored the possible influences of deficits in fine motor skills. The aim of our empirical study was, therefore, to investigate the influence of fine motor skills and how they may affect underachievement. We hypothesized that deficits in fine motor skills could possibly be mediated by persisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
7
0
4
Order By: Relevance
“…The variables in this study were specifically derived from the PUM framework, and sought to confirm the presence of particular variable combinations. Students without maladaptive competence or value beliefs may nonetheless underachieve because of many possible reasons, including but not limited to classroom climate (Stoeger et al, 2008), self‐regulation capabilities (Ritchotte et al, 2014), and peer group conformation (Swiatek, 2001). Expanding the analysis to include a wider array of variables could bring to light other types of students prone to underachievement, and it could also potentially uncover a multiplicity of motivational patterns leading to underachievement outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The variables in this study were specifically derived from the PUM framework, and sought to confirm the presence of particular variable combinations. Students without maladaptive competence or value beliefs may nonetheless underachieve because of many possible reasons, including but not limited to classroom climate (Stoeger et al, 2008), self‐regulation capabilities (Ritchotte et al, 2014), and peer group conformation (Swiatek, 2001). Expanding the analysis to include a wider array of variables could bring to light other types of students prone to underachievement, and it could also potentially uncover a multiplicity of motivational patterns leading to underachievement outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we extended previous findings by investigating the interaction in early academic skills, in a large, representative kindergarten sample, and in specific academic domains relevant to early childhood education. Previous findings by Stoeger et al (2008) were based on a selected sample of gifted fourth-graders' general scholastic achievement averaged over maths, language and science, while Cameron et al's (2015) findings were based on preschool children over a wider age range of two to five years, and excluded maths outcomes. Despite some differences in the aspects of FMS and EF examined across the studies, the general finding is largely consistent with an interactive account of EF and FMS contributing to academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that students from high-SES environments are more likely to discover their interests and develop confidence in STEM areas as their parents are capable of providing them with opportunities for exposure to science or related enrichment experiences (Ho et al, 2020; Miller & Kimmel, 2012). However, when gifted students do not have educational opportunities, such as challenging in-school programs or enriching extracurricular out-of-school programs, they might be at risk of not fully developing their learning potential (Stoeger & Ziegler, 2013; Subotnik et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%